Ets-1 binds cooperatively to the palindromic Ets-binding sites in the p53 promoter. - Baillat, D; Laitem, C; Leprivier, G; Margerin, C; Aumercier, M (2009)
Due to its autoinhibition for DNA binding, the Ets-1 transcription factor must interact with partners to enhance its affinity for DNA. In a study on the stromelysin-1 promoter, we showed that Ets-1 binds cooperatively to two Ets-binding sites (EBS) organized in palindrome, thereby circumventing the need for a binding partner to counteract autoinhibition. This leads to the formation of an Ets-1-DNA-Ets-1 ternary complex necessary for promoter activation. Here we show that Ets-1 also binds cooperatively to the EBS palindrome of the human p53 promoter, despite the presence of a degenerate EBS to which Ets-1 cannot otherwise bind. Transcriptional transactivation through this palindrome fully correlates to Ets-1 binding. Thus, the cooperative binding model that we initially proposed for the stromelysin-1 promoter may be a general mechanism of Ets-1 binding to palindromic EBS separated by 4bp and a way to counteract binding site degeneracy.